2016
DOI: 10.1016/j.jembe.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Surprising episodic recruitment and growth of Antarctic sponges: Implications for ecological resilience

Abstract: Sponges are the most conspicuous component of the Antarctic benthic ecosystem, a system under stress both from climate change and fishing activities. Observations over four decades are compiled and reveal extremely episodic sponge recruitmentand growth.Recruitment occurred under different oceanographic conditions on both sides of McMurdo Sound. Most of the sponges appear to have recruited in the late 1990s-2000. Observations from 2000 to 2010follow thirty years of relative stasis with very little sponge recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
84
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 58 publications
7
84
0
3
Order By: Relevance
“…Also benthic assemblages with much longer recovery times as those affected by volcanic activity at Deception Island did not reach richness and abundances of close areas after more than 30 yr or the newly opened Larsen areas that after 12 yr still shows low diversity and abundances patterns (Cranmer et al , Lovell and Trego , Gutt et al ). However, fast growth rates, population bursts, rapid colonisation and shifts in benthic structure have also been reported in a few species (Dayton , Rauschert , Gutt et al , Barnes , Dayton et al , ). Fillinger et al () reported a rapid glass sponge expansion in a pre‐existing community in a time lapse of four years; this increase was from 0.79 to 1.31 individuals m – 2 in glass sponge densities, and Dayton et al () also reported massive recruitment and high growth in glass sponges.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also benthic assemblages with much longer recovery times as those affected by volcanic activity at Deception Island did not reach richness and abundances of close areas after more than 30 yr or the newly opened Larsen areas that after 12 yr still shows low diversity and abundances patterns (Cranmer et al , Lovell and Trego , Gutt et al ). However, fast growth rates, population bursts, rapid colonisation and shifts in benthic structure have also been reported in a few species (Dayton , Rauschert , Gutt et al , Barnes , Dayton et al , ). Fillinger et al () reported a rapid glass sponge expansion in a pre‐existing community in a time lapse of four years; this increase was from 0.79 to 1.31 individuals m – 2 in glass sponge densities, and Dayton et al () also reported massive recruitment and high growth in glass sponges.…”
Section: Discussionmentioning
confidence: 96%
“…The relative constancy of environmental variables prevailing in Antarctic benthic ecosystems, together with the slow growth rates and population turnover registered in the vast majority of benthic invertebrates, has led to an image of a certain stability in structural patterns and a low speed in ecological processes in the Antarctic benthos (Arntz et al , Barnes and Conlan , Smale and Barnes ). Despite recent reports of fast colonisation and growth rates of some species following catastrophic environmental changes or in some artificial substrates (Rauschert , Raes et al , Gutt et al , Barnes , Dayton et al , , Fillinger et al , Quartino et al ), the experimental works carried out on colonisation and early succession showed a general pattern of very slow recruitment and development (Dayton , Pearse and Pearse , Barnes , Stanwell‐Smith and Barnes , Bowden , Bowden et al ). These reports suggest that, although there can be fast development in species or in higher taxa such as macroalgae and some sponges, at the community or assemblage level the general idea of slow processes can be maintained.…”
mentioning
confidence: 96%
“…In Svalbard, there is a much stronger influence of local species composition on recruitment than substratum type (natural or artificial) (Bałazy and Kukliński ). Recruitment can vary strongly between natural and artificial substrata in some cases, but this difference depends more on predator access to settlement surfaces than on the nature of the surface (Dayton et al ). Settlement plates at shallow locations in this study (Longyearbyen, Ny‐Ålesund, Kvadehuken) were accessible to benthic predators and thus show “realized recruitment” according to the terminology of Dayton et al ().…”
Section: Discussionmentioning
confidence: 99%
“…They grow slowly relative to other species at similar latitude and depth and live for long periods (Leys and Lauzon ; Krautter et al ). However, in Antarctica, hexactinellids undergo rapid recruitment and growth when environmental conditions increase the abundance of their food supply (Dayton et al , ). We did not observe episodic recruitment of hexactinellids, though our study was over a much shorter time period (18 vs. 50 yr) than Dayton et al (, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in Antarctica, hexactinellids undergo rapid recruitment and growth when environmental conditions increase the abundance of their food supply (Dayton et al , ). We did not observe episodic recruitment of hexactinellids, though our study was over a much shorter time period (18 vs. 50 yr) than Dayton et al (, ). We cannot exclude the possibility that Arctic hexactinellids undergo similarly episodic recruitment over time‐scales longer than our study.…”
Section: Discussionmentioning
confidence: 99%